Results after Repair of Functional Tricuspid Regurgitation with a Three-Dimensional Annuloplasty Ring - Elda Dzilic (MDPI AG, 2021)
Background: Tricuspid valve (TV) repair is the recommended treatment for severe functional tricuspid regurgitation (fTR) in patients undergoing left-sided surgery. For this purpose, a wide range of annuloplasty devices differing in form and flexibility are available. This study reports the results using a three-dimensional annuloplasty ring (Medtronic, Contour 3D Ring) for TV repair and analysis of risk factors. Methods: A cohort of 468 patients who underwent TV repair (TVr) with a concomitant cardiac procedure from December 2010 to January 2017 was retrospectively analyzed. Results: At follow-up, 96.1% of patients had no/trivial or mild TR. The 30-day mortality was 4.7%; it significantly differed between electively performed operations (2.7%) and urgent/emergent operations (11.7%). Risk factors for recurrent moderate and severe TR were LVEF < 50%, TAPSE < 16 mm, and moderate mitral valve (MV) regurgitation at follow-up. Preoperatively reduced renal function lead to a higher 30-day and overall mortality. Reoperation of the TV was required in six patients (1.6%). Risk factors for TV related reoperations were preoperative TV annulus over 50 mm and an implanted permanent pacemaker. Conclusions: TVr with the Contour 3D annuloplasty ring shows low TR recurrence and reoperation rates. Risk-factor analysis for the recurrence of TR revealed the importance of left- and right-ventricular function.